A Educação Física e a Base Nacional Comum Curricular: antigas e novas problematizações - Prietto, Adelina Lorensi (2021)
This study aims to investigate the Common Curricular National Base, in particular to analyze how the area of Physical Education is presented in the current BNCC, seeking to identify and analyze the education project presented in that Base for the area of School Physical Education. We also seek to highlight the contradictions and contributions to the training of students, in the stage of basic education, as well as to analyze the profile of the worker that BNCC intends to form and what are the possible impacts resulting from the proposed legislation for the pedagogical work in School Physical Education. As a research method, we use dialectical historical materialism. Carry out a bibliographic review; analysis of BNCC legislation and in particular, the analysis of the proposal for the area of Physical Education presented by BNCC. We found that the concept of Physical Education present at BNCC, advocates training based on the principles that support the capitalist social organization model from the needs of its productive restructuring, as its precepts aim at adapting students to the current form of sociability, where the educational process mediates the development of individuals to conform to the established way of life, with no intention of transforming it and educational policies follow the agenda of economic policies.